Проблема моделирования в экономических системах в условиях неопределенности - Тимофеев, В. А.; Кирій, В. В. (ХНУРЭ, 2013)
The problem of modelling in economic systems is considered. The different approaches to the construction of mathematical model such systems are researching. The porcedure of construction of mathematical models of economic systems on the base of critical approach is porposed.
Keywords: управление в экономических системах; синтез систем управления; метод неравенств; условия неопределенности; алгоритмические методы; оптимизационные методы